Ten Cases of Feline Mediastinal Lymphoma - MORISHITA, Keitarou; NAGAYA, Yusuke; SHOJI, Yuki; FUKUI, Kenta; TABATA, Katsutoshi; YASUKAWA, Kuniyoshi; UENO, Takashi; SHIMODA, Tetsuya (Journal of Animal Clinical Medicine, 2011)
From 2005 November through 2010 July, ten cases of feline mediastinal lymphoma which had been treated according to the University of Wisconsin-Madison chemotherapy protocol for dogs (UW 25) were surveyed retrospectively regarding complete remission rate, survival time, and adverse effects of this compound chemotherapy. The average complete remission rate was 90%. Six cats survived for less than one year, one of which is still alive. Another cat survived for over one year, and is still alive. Yet another cat survived for over two years, and is still alive. The remaining two survived for over three years, and one of them is still alive. In general, side effects were slight, and were cured with symptomatic treatment. This multi-agent protocol, UW 25, proved to be much better than conventional COP protocol in respect of survival time, showing that long-term survival could be achieved with its use.